The big rig : trucking and the decline of the American dream - Viscelli, Steve, 1974- (University of California Press, 2016)
"'The Big Rig' looks at what has happened to blue-collar jobs since the trucking industry was deregulated. Truckers are now working longer hours and for less pay than they were fifty years ago. Why do truckers accept these conditions and pay? Why can't they achieve what workers did in the past through collective action and union organization? Modern trucking has been sold as an entrepreneurial dream, but the reality has shown that there is no chance of upward mobility, with wages being driven down because of increasing competition and slim profit margins. Writing and researching from an on-the-ground perspective, Steve Viscelli took a job as a long-haul trucker to learn why trucking went from one of the best blue-collar jobs in the United States to one of the worst. However, what has happened to the trucking industry is not unique. This book tells the larger story of the dramatic rise of inequality and decreased mobility in the United States."--Provided by publisher